Antena SIW dengan Defected Ground Structure pada Frekuensi L-Band - Mia Maria Ulfah; Achmad Munir (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
In this paper, a bandwidth enhancement technique for Substrate Integrated Waveguide(SIW) antenna is attempted using Defected Ground Structure(DGS)by modifying the shape and geometry of the slot on the ground plane. In order to achieve wide bandwidth response of the antenna, a rectangular split ring incorporated with across shapes lots are employed as DGS. The quality factor (Q) of antenna increases as the substrate thickness decreases, which leads to narrow down bandwidth response of the SIW antenna. Therefore, the SIW antenna is simulated using multiple layers of FR4epoxydielectric substrate in overcoming the problem. The SIW antenna has a dimension of 171 mm×160.5mm, 4.905mm-height,and is intended to work at the center frequency of 2 GHz. Furthermore, the SIW antenna is excited by proximity coupling method which is connected to a 50Ω connector. Simulation result shows that the 575 MHz bandwidth could be achieved by the antenna with the proposed technique, in which the -10dB bandwidth response is ranged from the frequency of 1.675 GHz –2.25 GHz and the maximum gain is6.03 dBi at the frequency of 1.85 GHz,with bidirectional radiation pattern.